ISSUES OF STRATEGIC MANAGEMENT OF FOOD INDUSTRY ENTERPRISES IN THE NATIONAL ECONOMY (Marketing Journal, 2025)
This article explores the theoretical and practical aspects of strategic management in the activities of food industry enterprises within the national economy. The study analyzes the essence of strategic management, its modern models and mechanisms, as well as the specific features of strategic planning and decision -making processes in food industry enterprises. The article substantiates the importance of enhancing enterprise competitiveness, identifying directions for innovative development, ensuring produ ction efficiency, and forming a flexible management system that meets market demands. In addition, it presents proposals for improving strategic management in the sector, rational use of resources, and strengthening enterprise sustainability. The research results have significant scientific and practical importance for the development of food industry enterprises and for ensuring overall economic stability.
Keywords: strategic management; food industry; enterprise efficiency; innovative development; competitiveness; planning; resource utilization; sustainability; economic reforms; management